Artificial Intelligence and the Teaching Process for Economics Students - Vinueza-Vinueza, Santiago (2026)
Artificial intelligence drives knowledge, facilitates the comparison of diverse perspectives, and provides information tailored to student needs. In the teaching process, it promotes various strategies, tools, and methodologies that are revolutionizing the educational field. In this sense, within university settings, the teacher acts as a guide and facilitator, shaping a pedagogical and cognitive process. This approach is grounded in an ethical awareness that avoids excessive dependence, inequality, or misinformation. This study employed a quantitative approach with a non-experimental design. The research was cross-sectional, collecting data at a single point in time, and had an explanatory scope aimed at addressing the causes of social phenomena related to higher education and Artificial Intelligence (AI). The population consisted of 243 university students enrolled in the second and third semesters of the Statistics, Economics, and Finance programs at the Central University of Ecuador. To obtain a sample size of 149 students, simple random sampling (SRS) and proportional stratified sampling were used to ensure equitable representation according to academic level (68 second-semester students and 81 third-semester students). The results show that, although students demonstrate a moderate level of ethical awareness, gaps remain in their comprehensive understanding of some theoretical constructs related to the ethical use of AI. This situation highlights the need to incorporate specific content into educational programs aimed at strengthening ethical considerations in the use of these technologies.